2014
DOI: 10.1080/10494820.2014.937344
|View full text |Cite
|
Sign up to set email alerts
|

Podcasting in a virtual English for academic purposes course: learner motivation

Abstract: In this study we explored the effect of podcasting on the motivation of the students in an online English for Academic Purposes (EAP) course at university level (N= 179). By using a mixed-method approach, we analysed the data collected on the learners' impressions about using podcasts as a learning tool. The findings on the IMM survey revealed that males found podcasting significantly more relevant and attractive than females. Females, on the other hand, were significantly more satisfied with using podcasts in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 29 publications
2
18
1
Order By: Relevance
“…Because of the ease accessibility of Web-based technology in Iran and its ubiquitousness, there has been a noticeable transformation in the learning of students . Especially among the young generation, elearning is seen as the building block that supports the structure of modernization (Asoodar, Marandi, Vaezi, & Desmet, 2014 ;Asoodar, Atai, & Vaezi, 2015).…”
Section: Learner Dimensionmentioning
confidence: 99%
“…Because of the ease accessibility of Web-based technology in Iran and its ubiquitousness, there has been a noticeable transformation in the learning of students . Especially among the young generation, elearning is seen as the building block that supports the structure of modernization (Asoodar, Marandi, Vaezi, & Desmet, 2014 ;Asoodar, Atai, & Vaezi, 2015).…”
Section: Learner Dimensionmentioning
confidence: 99%
“…Specifically, this study investigates the use of both wikis and blogs because this approach closely matches the reality for learners today, in which text messages, e-mails, blogs, and wikis are popular methods of day-to-day communication (Oblinger & Oblinger, 2005;Asoodar, Marandi, Atai, & Vaezi, 2014;Asoodar, Marandi, Vaezi, & Desmet, 2014).…”
Section: Significance Of This Studymentioning
confidence: 98%
“…Several researchers (Kemp, Mellor Kotter & Oosthoek, 2011;Nie, Cashmore & Cane, 2008;Prensky, 2009) have pointed to the novelty factor of experiential learning as a main stimulus for learning. A number of researchers have also found that the use of podcasts in education can increase intrinsic motivation (Asoodar, Marandi, Vaezi & Desmet, 2014;Dale & Povey, 2009;McMinn, 2008;O'Bryan et al, 2007;Royer 2009). In contrast to extrinsic motivation, which relies on good grades as a reward, intrinsic motivation is achieved when tasks are interesting and challenging, (O'Bryan et al, 2007).…”
Section: Motivation and Confidencementioning
confidence: 99%